Hubungan Tingkat Pengetahuan Gizi Pengasuh dengan Tingkat Konsumsi Energi Protein dan Status Gizi Batita di Wilayah Puskesmas Undaan Kabupaten Kudus - Hariyani, Rina (2016)
Background : Children aged 1-3 years are most vulnerable group to nutritional problems. Nutritional status of children can be affected by food intake and infection as direct causes, and education and knowledge as indirect causes. Preliminary survey in January 2015 showed that 24.52% of mothers in region of Undaan Primary Health Service worked so that children cared by caregivers. The prevalence of malnutrition status in 2013 in region of Undaan Primary Health Service Kudus District was 17.56%, which means vulnerable to nutrition problems. Objective : This research aims to determine the relationship between level of caregivers' nutrition knowledge and level of energy protein consumption and nutritional status of toddlers. Research Method : This research was a cross-sectional research conducted on May-July 2015. Subjects were non-mother caregivers and toddlers as many as 44 people, taken with stratified random sampling method. Caregivers in this research was the caregivers other than mother and still had family relationship with toddlers. The research instruments were questionnaire to measured nutrition knowledge and nonconsecutive 24 hours food recall 4 times while the research tool was balance weighing scale to the nearest of 0.1 kg. Data were analysed with Pearson Product Moment Correlation. Results : 72.7% caregivers had insufficient nutritional knowledge level, 31.8% toddlers had energy consumption level above requirement, 70.5% toddlers had protein consumption level above requirement, and 86.4% toddlers had good nutritional status (W/A). There is no correlation between caregivers's nutrition knowledge and the level of energy consumption (p = 0.843), protein (p = 0.511), and toddlers nutritional status (p = 0.248). Conclusion : The level of nutrition knowledge is not related significanly to the level of consumption of energy, protein and nutritional status of toddlers. Health workers are expected to further increase the frequency of nutritional counseling to improve the nutritional knowledge of caregivers.